The relationship between physical activity, orthostatic blood pressure reactions and subclinical atherosclerosis : the Swedish CArdioPulmonary bioImage Study (SCAPIS) - Kharraziha, Isabella ; 0000-0001-9150-1289; Memarian, Ensieh; Ekblom, Örjan; Gottsäter, Anders; Engström, Gunnar; Hamrefors, Viktor ; 0000-0002-8475-0866 (Journal of Human Hypertension, 2025)
An abnormal blood pressure (BP) response on standing is associated with atherosclerotic cardiovascular disease (CVD). The role of physical activity (PA) on orthostatic BP-reactions and its relation to subclinical atherosclerosis is unclear. We aimed to assess the association between PA and orthostatic BP-reactions, and whether PA modifies the relationship between orthostatic BP-reactions and subclinical atherosclerosis. A total of 5,396 middle aged subjects from the population-based SCAPIS-study were included. Associations between orthostatic BP-response and accelerometer-derived PA were studied using linear regression. Interaction analyses were performed to study modifying effects of PA on the relationship between orthostatic BP-response and subclinical coronary atherosclerosis, assessed by coronary artery calcium score (CACS). Moderate to vigorous PA (MVPA) was associated with less pronounced orthostatic systolic BP (SBP) increase but more pronounced orthostatic diastolic BP increase after adjusting for age, sex, total wear time, proportion weekend days and season (Beta per 1%-increase(mmHg):0.12; p = <0.01 and −0.06; p = 0.02, respectively). Subjects with high MVPA were less likely to have orthostatic hypertension (OHTN), but more likely to have orthostatic hypotension (OH; p = 0.002 for both). Individuals with higher CACS were more likely to have OH (p = 0.041) but not OHTN (p = 0.276). There were no interactions of PA on the association between orthostatic BP-response and CACS. In conclusion, physically active middle-aged individuals are less likely to show inappropriate SBP-increase upon standing, but more likely to have excessive SBP-decrease. PA does not modify the association between orthostatic BP-response and subclinical atherosclerosis. The relationship between PA, orthostatic BP and CVD is likely to be complex.